(untitled) (Journal of the Bangladesh Agricultural University, 2016)
The experiment was conducted at Ulipur, Kurigram and Gabtoli, Bogra for two consecutive rabi seasons (2010-11 to 2011-12) to observe the performance of some high yielding garlic varieties ( BARI Roshun 1, BARI Roshun 2, BAU Roshun 1 and BAU Roshun 2) including local variety at farmers field. In Kurigram, the highest yield (8.11 and 8.04 t ha-1 during two successive years) was obtained from BARI Roshun 2, which differed significantly from other varieties. In Bogra, the highest yield (12.01 and 11.82 t ha-1 during two successive years) was obtained from BAU Roshun 2, which differed significantly from other varieties but in the second year it was statistically identical to BAU Roshun 1. In Kurigram, the highest gross return (Tk. 405500 and 241237 ha-1) and the highest gross margin (Tk. 308325 and 97664 ha-1) were obtained from BARI Roshun 2 where as in Bogra, the highest gross return (Tk. 960000 and 574000 ha-1) and the highest gross margin (Tk. 826217 and 433081 ha-1) were obtained from BAU Roshun 2 during two successive years. The lowest gross return and gross margin was obtained from local variety at both locations. J. Bangladesh Agril. Univ. 12(2): 235-239, December 2014